2019
DOI: 10.21164/pomjlifesci.634
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the dietary habits of English programme medical students in their first year of studies

Abstract: Introduction: Human nutrition depends on many factors. Cultural practices, socio-psychological and economic factors play important roles in development of correct nutrition patterns. Eating habits are formed most strongly during childhood and adolescence. When young people begin university study, their way of life changes significantly. In this study group, not only do the necessities of independent living and food preparation occur, but also a change the country of residence. The aim of the study was to inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
(43 reference statements)
0
1
0
Order By: Relevance
“…Many other studies have shown that non-US medical students frequently skip breakfast. [10][11][12][13] The prevalence of breakfast consumption among US medical students has not been reported previously in the literature. Do US medical students similarly frequently skip breakfast?…”
Section: Introductionmentioning
confidence: 89%
“…Many other studies have shown that non-US medical students frequently skip breakfast. [10][11][12][13] The prevalence of breakfast consumption among US medical students has not been reported previously in the literature. Do US medical students similarly frequently skip breakfast?…”
Section: Introductionmentioning
confidence: 89%